Information Disclosure and Questionnaires in Public Tenders - Greve, T. (Penn State, 2025)
Public tenders, particularly for non-standardized or complex projects, typically in- volve uncertainty and unforeseen costs (hereafter, adaptation costs), that might not even be fully known to the bidders themselves at the time of bidding. We consider a first-score auction with a pre-qualification stage, where the procurer can obtain information on the likely adaptation costs from the bidders and can choose to disclose its assessment of that information to the bidders before the bidding stage starts. Under certain assumptions, we show that the procurer benefits from having information about the adaptation costs, but it will be to its advantage if some of that information is withheld from the bidders - following the pre-qualification stage - rather than sharing all of it. If one see the underlying change in the adaptation cost as the occurrence of many small deviations taking place during construction, then information on the adaptation cost can be obtained via questionnaires. These are designed as a tool for exposing the in- herent tendency of the bidder to diverge from the planned or desired action, such that the adaptation cost may be estimated. Further, since the focus is on standard deviation of answers rather than on means, the incentive for misinformation on the side of the bidder is largely eliminated.